From the battlefront to the bridal suite [ media coverage of British war brides, 1942-1946 - Friedman, Barbara G. , 1963- (University of Missouri Press, 2007)
"Friedman reexamines the stories surrounding the influx of British war brides brought back to the United States by American GIs after WWII with a focus on media representations of sexuality and marriage in wartime, showing how mass media interpretations turned from public suspicion of war brides to popular acceptance"--Provided by publisher